2015
DOI: 10.1108/jamr-03-2014-0021
|View full text |Cite
|
Sign up to set email alerts
|

Socially responsible stocks: a boon for investors in India

Abstract: Purpose – The purpose of this paper is to empirically examine the performance of socially responsible stocks portfolio vis-à-vis portfolios of general companies in the Indian stock market. Design/methodology/approach – The study has used absolute rate of return as well as various risk adjusted measures like Sharpe ratio, Treynor ratio, Jensen’s α, Information ratio, Fama’s decomposition measure and dummy regression model to evaluate the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 9 publications
(14 reference statements)
0
36
0
Order By: Relevance
“…There is a burgeoning interest in the concept of CSR in recent years. The wide popularity of CSR is attributable to global warming, environmental degradation, corporate frauds and global financial crisis (Tripathi and Bhandari, 2015). According to Aguinis and Glavas (2012), CSR means organizational endeavors that consider stakeholders' expectations in social, environmental and economic contexts.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…There is a burgeoning interest in the concept of CSR in recent years. The wide popularity of CSR is attributable to global warming, environmental degradation, corporate frauds and global financial crisis (Tripathi and Bhandari, 2015). According to Aguinis and Glavas (2012), CSR means organizational endeavors that consider stakeholders' expectations in social, environmental and economic contexts.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…This shows nothing but an indication of investors' positive attitude towards socially responsible companies. The positive performance by GREENEX and ESG (environment, social and governance) index reported during the crisis period (Tripathi and Bhandari, 2015) indicates the increasing demand for stocks of socially responsible companies in the Indian stock market. This indication supports that increasing the financial performance of socially responsible companies might attract even those investors who are not bothered about social or environmental issue (Lewis and Mackenzie, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…As far as literary work is concerned, the importance of social responsibility can be traced in diverse contexts where different antecedents of social responsibility have been proposed. For example, studies on growth and performance of SRI funds vis-à-vis non-SRI funds (Kempf and Osthoff, 2007;Revelli and Viviani, 2015;Lewis and Mackenzie, 2000;Tripathi and Bhandari, 2015), the relationship between institutional settings and corporate social responsibility (Demirbag et al, 2017), the effect of religious belief and SRI on the cost of debt (Li et al, 2019), explanation on the adoption of similar supplier development (SD) to address the social issues faced by local supply chains of developing countries (Yawar and Kauppi, 2018), the relationship between demography of consumers and social responsibility (Singh, 2009) etc. are a few of the literature works which have attracted global attention on social well beings.…”
Section: Introductionmentioning
confidence: 99%
“…Chen ( 2008) compared the green core competence, green product innovation performance, green process innovation and green image of Taiwanese large enterprises with small and medium enterprises in information and electronic industry found that the influence of all these variables of SME's was significantly less than those of large enterprises in Taiwan. While comparing the socially responsible stocks with other portfolios, socially responsible stocks portfolios are found higher return with lower during crisis and post-crisis (Tripathi & Bhandari, 2015). In contraction to this (Jain et al, 2019) found that sustainable indices and conventional indices are integrated and there is no significant difference in the performance between sustainable indices and conventional indices.…”
Section: Sustainability Indicesmentioning
confidence: 71%
“…"Socially Responsible Investing, also known as sustainable, socially conscious, green or ethical investing, is any investment strategy which seeks to consider both financial return and social good" (Jain & Rohra, 2016). In recent years, the concept of Socially Responsible Investment has gained more popularity because of the increasing impact of global warming, climate change, environmental degradation, as a result, more investors making their investment by considering Environmental, Social, and Governance Factors (Tripathi & Bhandari, 2015). A socially responsible investor not only looks for return/wealth maximization but also encourages environmental, social, and governance practices of corporates, it has a long-term consequence on companies' financial performance (Jain & Rohra, 2016).…”
Section: Introductionmentioning
confidence: 99%